Effects of protein A immunoadsorption in patients with chronic dilated cardiomyopathy - Dösch, Andreas; Müller, Susanne; Konstandin, Mathias; Celik, Sultan; Kristen, Arnt; Frankenstein, Lutz; Göser, Stefan; Kaya, Ziya; Zugck, Christian; Dengler, Thomas; Katus, Hugo (Journal of clinical apheresis, 2010)
Objectives: The objective of this study was to investigate functional effects of immunoadsorption (IA) in patients with chronic nonfamilial dilated cardiomyopathy (DCM) regarding clinical and humoral markers of heart failure. Background: IA has been shown to induce early hemodynamic improvement in patients with nonfamilial dilated cardiomyopathy (DCM). Methods: We performed IA using protein A agarose columns on five consecutive days in 51 patients with chronic DCM, congestive heart failure of NYHA class ≥ II, left ventricular ejection fraction ≤50%, and mean time since initial diagnosis of 5.0 ± 5.8 years. Results: Immediately after IA, immunoglobulin G (IgG) decreased by 89.4% and IgG3 by 66.7% (both P < 0.0001). Median NT-pro BNP was reduced from 1230.0 ng L−1 at baseline to 829.0 ng L−1 after 6 months (P < 0.0001). Also mean left ventricular ejection fraction (LVEF) was significantly improved (26.3% ± 9.4% to 28.7% ± 11.4% after 6 months, P = 0.016) and LVEF improved ≥5% (absolute) in 21 of 51 (41.2%) patients. After 6 months, bicycle spiroergometry showed a significant increase in exercise capacity from 82.0 ± 30.8 Watts to 93.1 ± 34.3 Watts (P = 0.008) while VO2max rose from 15.0 ± 4.1 to 16.4 ± 4.8 mL min−1 kg−1 (P = 0.01). Conclusions: In this study, on heart failure patients with nonfamilial DCM, IA therapy significantly improved clinical and humoral markers of heart failure severity. These promising results may be due to the selected study population, with a shorter disease duration and the higher amount of IgG 3 reduction. Future blinded prospective multicenter studies are necessary to identify those patients that benefit most.